Online Food Delivery Services: An Analysis of Consumer Intentions in Chitwan - Mahesh Prasad Upadhyay (Journal of Balkumari College, 2025)
The rapid expansion of the online food delivery (OFD) industry, powered by technological innovation and shifting consumer lifestyles, has significantly influenced consumption patterns worldwide. However, in developing countries like Nepal—particularly in semi-urban areas such as Chitwan—research on consumer behavior regarding OFD services remains limited. Specifically, it explores the roles of Performance Expectancy, Effort Expectancy, Social Influences, and Facilitating Conditions in shaping consumer decisions. A descriptive and causal-comparative research design was adopted, and primary data were collected from 250 OFD users in Chitwan through structured questionnaires administered via interviews and mail surveys. Findings reveal that Social Influences have the strongest positive impact on Behavioral Intention (r = 0.591, p < 0.01), underscoring the significance of peer recommendations, online reviews, and social media in driving OFD adoption. Performance Expectancy also shows a moderate positive relationship (r = 0.343, p < 0.01), indicating that perceived convenience and time efficiency are valued by consumers. Conversely, Effort Expectancy (r = -0.150, p < 0.05) and Facilitating Conditions (r = -0.239, p < 0.01) exhibit negative correlations with Behavioral Intention. This suggests that perceived complexity and inadequate support infrastructure may hinder usage. The regression model confirms the statistical significance of all variables (R² = 0.427), with Social Influences (B = 0.605) emerging as the most influential predictor, followed by Facilitating Conditions (B = 0.421), Performance Expectancy (B = 0.195), and Effort Expectancy (B = -0.160). These results align with international studies on OFD behavior but also highlight localized challenges, such as infrastructural limitations and digital literacy barriers, which influence adoption in Chitwan. In conclusion, the study successfully identifies and evaluates the key determinants of behavioral intention among OFD users in Chitwan. It emphasizes the critical role of social dynamics, technological accessibility, and ease of use in fostering positive consumer attitudes. The findings provide actionable insights for OFD service providers to enhance user engagement, improve platform usability, strengthen customer support, and leverage social influence to boost adoption and long-term customer retention in similar semi-urban markets.